Hemoglobin Protects Enamel against Intrinsic Enamel Erosive Demineralization - Carvalho, Thamyris Souza; Araújo, Tamara Teodoro; Oliveira Ventura, Talita Mendes; Dionizio, Aline; Frazão Câmara, João Victor; Moraes, Samanta Mascarenhas; Leme, Júlia Chaparro; Grizzo, Larissa Tercilia; Crusca, Edson [UNESP]; Tanaka Shibao, Priscila Yumi; Marchetto, Reinaldo [UNESP]; Henrique-Silva, Flavio; et al. (My University, 2024)
Introduction: This study investigated the changes in the acquired enamel pellicle (AEP) proteome when this integument is formed in vivo after treatment with sugarcane-derived cystatin (CaneCPI-5), hemoglobin (HB), and a statherin-derived peptide (StN15), or their combination and then exposed to an intrinsic acid challenge. The effectiveness of these treatments in preventing intrinsic erosion was also evaluated. Methods: Ten volunteers, after prophylaxis, in 5 crossover phases, rinsed with the following solutions (10 mL, 1 min): control (deionized water-H2O) – group 1, 0.1 mg/mL CaneCPI-5 – group 2, 1.0 mg/mL HB – group 3, 1.88 × 10−5 M StN15 – group 4, or a blend of these – group 5. Following this, AEP formation occurred (2 h) and an enamel biopsy (10 µL, 0.01 M HCl, pH 2.0, 10 s) was conducted on one incisor. The biopsy acid was then analyzed for calcium (Arsenazo method). The vestibular surfaces of the other teeth were treated with the same acid. Acid-resistant proteins in the residual AEP were then collected and analyzed quantitatively via proteomics. Results: Compared to control, treatment with the proteins/peptide, mixed or isolated, markedly enhanced acid-resistant proteins in the AEP. Notable increases occurred in pyruvate kinase PKM (11-fold, CaneCPI-5), immunoglobulins and submaxillary gland androgen-regulated protein 3B (4-fold, StN15), Hb, and lysozyme C (2-fold, StN15). Additionally, a range of proteins not commonly identified in the AEP but known to bind calcium or other proteins were identified in groups treated with the tested proteins/peptide either in isolation or as a mixture. The mean (SD, mM) calcium concentrations released from enamel were 3.67 ± 1.48a, 3.11 ± 0.72a, 1.94 ± 0.57b, 2.37 ± 0.90a, and 2.38 ± 0.45a for groups 1–5, respectively (RM-ANOVA/Tukey, p < 0.05). Conclusions: Our findings demonstrate that all treatments, whether using a combination of proteins/peptides or in isolation, enhanced acid-resistant proteins in the AEP. However, only HB showed effectiveness in protecting against intrinsic erosive demineralization. These results pave the way for innovative preventive methods against intrinsic erosion, using “acquired pellicle engineering” techniques.
Keywords: Acquired enamel pellicle; Hemoglobin; Proteomics; Tooth wear